The Effect of Nonsurgical Therapy of chronic periodontitis on Hemoglobin A1c Levels in Persons With Type (2)Diabetes (Clinical study) - يوسف, تهامة; المرعي, منيف; ابراهيم, عمار (Latakia University Journal -Medical Sciences Series, 2021)
BACKGROUND: Diabetes and periodontal disease are two common diseases with high prevalence rates. Recent evidence has showna bidirectional relationship between diabetes and periodontitis. OBJECTIVE:: To determine if nonsurgical periodontal treatment reduces levels of glycated hemoglobin (HbA1c) in persons with type 2 diabetes. METHODS: The main sample of the study consisted of (20) patients ,with type 2 diabetes and chronic periodontitis ,Reviewers for the Department of Periodontology in Tishreen University . The main sample of the study was divided into two groups: , the poorly controlled group [glycated hemoglobin (HbA1c)7-8 %] included (10) patients and the non-controlled group (HbA1c>8-9%) included (10) patients . All subjects received non-surgical periodontal therapy(oral hygine instructions,scaling and root planing). (HbA1c) was measured at baseline and 3 months after the treatment. periodontal probing depth(PD)was recorded at baseline and 3 months after the treatment. RESULTS: The HbA1c of diabetic patients reduced significantly 3 months after treatment .The HbA1c of the non-controlled group reduced significantly3 months after treatment 8.61 % compared with the HbA1c of the poorly controlled group 7.36%((p-value<0.05 ) . At 3 months after treatment, ( PD) of both groups significantly reduced (p-value<0.05 ). The periodontal probing depth (PD) of the non-controlled group reduced significantly3 months after treatment compared with (PD) of the poorly controlled group(p-value<0.05 ). CONCLUSIONS: Non-surgical periodontal treatment improved and maintained the gingival and periodontal health of patients with Type (2) diabetes ,and improve glycemic control in patients with type 2 diabetes and chronic periodontitis.